Re-evaluation of initial masking level in pure tone audiometry - Rahmat, Sarah; Jamaluddin, Saiful Adli; Dzulkarnain, Ahmad Aidil Arafat (2011)
There are several methods of masking which can be applied in pure tone audiometry, and currently different audiological settings apply different initial masking levels. A high level of initial masking could lead to potential overmasking and reaching audiometric limits before a plateau can be established. The purpose of this study is to establish the optimum initial masking level that can be used in “Plateau Method” of masking. The Minimum Effective Masking Level (MEML) of 30 normal hearing ears was determined at octave frequencies from 250Hz to 4000Hz. Mean MEML for the octave frequencies ranged from -1.8 to 0.7 dB SL. There were significant differences of MEML between 250 Hz and 2 KHz, and 250 Hz and 4 KHz (P <0.05) with higher MEML recorded at higher frequencies as compared to 250Hz. MANOVA revealed no significant difference of MEML between male and female across frequencies (P<0.05). Pearson correlation revealed a strong positive significant linear relationship between pure tone level and masker level for all frequencies (P<0.05; 0.95<r<1.0) which suggests that the narrowband noise used is effectively masking the pure tone signals. The highest recorded MEML is 5dB SL at all octave frequencies. Taking a conservative approach, this value was used in the calculation of optimum initial masking level in addition to 5 dB to ensure significant threshold shift. It is recommended that 10 dB SL of initial masking level is applied in audiology clinics in Malaysia as it is adequate to effectively mask the pure tone threshold.